THE EFFECTIVENESS OF USING INDIVIDUAL LEARNING IN TEACHING LISTENING - Sulistia Wardani (Universitas Pendidikan Mandalika, 2016)
This research was aimed to find out the effectiveness of using individual learning in teaching listening of song and conversation. The research was experimental research and the design that was used was the one group pre-test post-test design. The population of the study was the second grade students of MTs. NW. Lingsar which consisted of one class and this research took all population as sample, consisting of 27 students. Data of the research were primarily gathered from the pre-test and post-test of listening test, in which the result of pre-test was used as control class and the result of post-test was as the experimental class. In analyzing data of the research, the researcher used t–test formula. Based on the analysis, it was gotten that t-test score was 27.76 with the degree of freedom (df) = 26 and t-table was 2,056 at the significant level =0.05. Because t-test is higher than t-table meaning that individual learning is effective in teaching listening at the second grade students’ of MTs. NW. Lingsar in the academic year 2017/2018.